The Effect of Cryogenic Cooling on Surface Roughness of Titanium Alloy: A Review - Razak, M. S.; Sulaiman, M. A.; Mat, S. A.; Ramle, Z.; Mohamad, E.; Salleh, M. R. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Titanium alloys are attractive materials due to their uniquely high strength–weight ratio, which is maintained at elevated temperatures. Titanium alloys represent a significant metal portion of the aircraft structural and engine components. When these critical structural components in aerospace industry are manufactured with the objective to reach high reliability levels, surface roughness is one of the most relevant parameters used for evaluating the quality of finish machined surfaces. Application of coolant and lubricant in manufacturing operations such as turning has been proven to improve the surface roughness of the work materials. In this review, application of cryogenic coolant in machining was investigated in detail in terms of application methods in material removal operations which is turning process on titanium alloy and its effects on surface roughness of the work materials. As a result, cryogenic cooling has been determined as one of the most favourable method for material cutting operations due to being capable of considerable improvement in surface finish through reducing the value of surface roughness, consequently, boost the functional performance of the components.